PERAN INFLUENCER DALAM DIPLOMASI DIGITAL: STUDI KASUS TREND ‘AURA FARMING’ PACU JALUR SERTA POTENSI WISATA BUDAYA DI INDONESIA - Rizfi Nur Rohim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study comprehensively examines the important role of influencers or content creators as new actors in digital diplomacy through a case study of the viral phenomenon 'Aura Farming' Pacu Jalan. By analyzing how content created by influencers was able to transform Pacu Jalur from a local tradition in Kuantan Singingi, Riau Province to a widely known cultural tourism attraction, this study highlights the shifting role of actors in today's diplomacy. Through a content analysis approach to narratives and visuals on social media, as well as a literature review on soft power and public diplomacy, this study shows that influencers now function as effective agents of informal diplomacy. Key findings show that influencers are able to promote Indonesian tourism, drive the local economy, and strengthen the nation's positive image in the global arena. This research recommends a more structured synergy between the government and influencers to optimize the promotion of culture and tourism in the digital age.